Atlantor, a new generic name for Barbus reinii Günther, 1874 from Morocco(Teleostei: Cyprinidae) - Borkenhagen, Kai; Freyhof, Jörg (Zootaxa, 2023)
Atlantor, new genus, is proposed for Barbus reinii from the Atlantic basin in Morocco. The sole species of the genus is clearly separated from related genera based on its phylogenetic position, and from Carasobarbus, Mesopotamichthys and Pterocapoeta in its morphological characters. Atlantor was previously included in Labeobarbus, making this genus paraphyletic with respect to several genera from Western Asia and North Africa. With the description of Atlantor, all these genera become monophyletic. Within Torinae, Atlantor can be diagnosed by having 5½ branched anal-fin rays, modally 8½ branched dorsal-fin rays, two pairs of long barbels, and by its distinct phylogenetic position.